Remotion of the antibiotic tetracycline by titania and titania-silica composed materials - Brigante, Maximiliano Eduardo (2011)
Removal of the antibiotic tetracycline (TC) by TiO 2 and the mesoporous binary system TiO 2-SiO 2 have been studied in batch experiments by performing adsorption isotherms/kinetics and photodegradation kinetics under different conditions of pH, supporting electrolyte concentration, temperature, adsorbent amount, and TiO 2-loading. On the one hand, the adsorption of TC on the studied materials is strongly dependent on pH, increasing as pH decreases. The adsorption mechanism, controlled by diffusion processes, is strongly related to electrostatic attractions and H-bond formations mainly between amide, carbonylic and phenolic groups of the antibiotic and the functional groups of TiO 2. The adsorption capacity at constant pH increases in the order TiO 2